Imaging Reporters for Proteasome Activity Identify Tumor- and Metastasis-Initiating Cells - Amanda C. Stacer; Hanxiao Wang; Joseph Fenner; Joseph S. Dosch; Anna Salomonnson; Kathryn E. Luker; Gary D. Luker; Alnawaz Rehemtulla; Brian D. Ross (Molecular Imaging)
Tumor-initiating cells, also designated as cancer stem cells, are proposed to constitute a subpopulation of malignant cells central to tumorigenesis, metastasis, and treatment resistance. We analyzed the activity of the proteasome, the primary organelle for targeted protein degradation, as a marker of tumor- and metastasis-initiating cells. Using human and mouse breast cancer cells expressing a validated fluorescent reporter, we found a small subpopulation of cells with low proteasome activity that divided asymmetrically to produce daughter cells with low or high proteasome activity. Breast cancer cells with low proteasome activity had greater local tumor formation and metastasis in immunocompromised and immunocompetent mice. To allow flexible labeling of cells, we also developed a new proteasome substrate based on HaloTag technology. Patient-derived glioblastoma cells with low proteasome activity measured by the HaloTag reporter show key phenotypes associated with tumor-initiating cells, including expression of a stem cell transcription factor, reconstitution of the original starting population, and enhanced neurosphere formation. We also show that patient-derived glioblastoma cells with low proteasome activity have higher frequency of tumor formation in mouse xenografts. These studies support proteasome function as a tool to investigate tumor- and metastasis-initiating cancer cells and a potential biomarker for outcomes in patients with several different cancers.